INCREASING KNOWLEDGE ABOUT BODY RESILIENCE IN FACING DIABETES MELLITUS IN THE ELDERLY COMMUNITY RW 7 WONOKROMO VILLAGE: PENINGKATAN PENGETAHUAN TENTANG KETAHANAN TUBUH MENGHADAPI DIABETES MELLITUS DI KOMUNITAS LANSIA RW 7 KELURAHAN WONOKROMO - Effendi; Budhi Setianto; Agus Aan Adriansyah; Difran Nobel Bistara (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Surabaya is in 9th place among the top 10 places with diabetes in Indonesia, with a prevalence of 6.8. The elderly community in RW 07 Wonokromo Village is a community whose members experience degenerative diseases, such as diabetes. Therefore, there is a need for activities to empower the elderly community to become independent elderly people. Objective: This activity aims to increase knowledge about the body's resilience in preventing diabetes in old age. Method: This activity was held in the form of counseling and joint exercise activities which were participated in by the elderly community of RW 07, Wonokromo Village. The evaluation of this activity used a pre-test and post-test, and then discussion session. All data were analyzed using paired-T tests with α =5%. Results: This activity had a positive impact as evidenced by an increase in participants' knowledge from an average pretest score of 63.8% to a post-test of 85.8%. The results of the paired-T test showed that there was a difference in the level of knowledge before and after the education was provided (p=0.000). Conclusion: This activity was able to increase participants' knowledge in maintaining body resilience in preventing diabetes in old age.